2019
DOI: 10.1039/c8ra07943a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and activity performance of nickel-loaded spent FCC catalyst for pine gum hydrogenation

Abstract: A Ni-based catalyst supported over a spent fluid catalytic cracking (FCC) catalyst was prepared by a wet impregnation method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…In the oil refinery, the fluid catalytic cracking (FCC) is an important secondary conversion procrss 1 4 . The crude oil can be converted into the valuable small molecules products, which is an essential process for gasoline production 5 . In the FCC process, the catalytic activity of FCC catalyst decreases after several cycles.…”
Section: Introductionmentioning
confidence: 99%
“…In the oil refinery, the fluid catalytic cracking (FCC) is an important secondary conversion procrss 1 4 . The crude oil can be converted into the valuable small molecules products, which is an essential process for gasoline production 5 . In the FCC process, the catalytic activity of FCC catalyst decreases after several cycles.…”
Section: Introductionmentioning
confidence: 99%
“…77-1551). 17 Additionally, a small amount of zeolite ZSM-5, Al 2 O 3 , and SiO 2 was observed. The spent FCC catalyst was mainly composed of stable zeolite Y that indeed has been used in cracking and hydrocracking catalysts and has an internal pore structure, an acidic site that promotes the C–C cleavage and hydrogen transfer affecting the degradation of large polymers to moderate compounds.…”
Section: Resultsmentioning
confidence: 97%
“…The results indicated that the role of the strong Brønsted acid catalyst was enhanced to improve the catalytic activity to cleave C–C bonds from the medium-length hydrocarbon chain to smaller compounds, after which the effect of high temperature accelerated the secondary cracking reaction, resulting in a decrease in liquid yields and an increase in gas yields. 17 , 18 Furthermore, it is worth noting that the slight appearance of a carbonaceous layer increased with the increase in spent FCC to pyrolytic pyrolysis of WPEW due to the oligomerization and aromatization of alkanes in the catalyst pore structure. Compared with the use of spent FCC and noncatalytic pyrolysis, it was found that using spent FCC catalyst decreased both the liquid and solid yields, while the yield of gaseous compounds was increased due to the role of the FCC catalyst in thermal breakdown by free radicals at moderate temperatures enhancing the C–C degradation of the polymer chains into short hydrocarbon chains.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations